Pengaruh Pengelolaan Keuangan Daerah terhadap Akuntabilitas Kinerja pada Satuan Kerja Perangkat Daerah Kabupaten Badung - Yasa Wirama, I Made; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 29 No 1 (2019)DO - 10.24843/EJA.2019.v29.i01.p02, 2019)
The purpose of this study is to determine the effect of regional financial management on performance accountability in the regional work unit of Badung Regency. To determine the influence of regional financial management, four variables are used to measure it, namely budget planning (X1), implementation/implementation of the budget (X2), reporting/budget accountability (X3), and performance evaluation (X4). Method of determined  sample in this study used purposive sampling technique, so that obtained a total sample of 100 people consisted of the Regional Government Budget Team. The data analysis technique used to test the hypothesis of this research is  multiple linear regression analysis. The results showed that budget planning, implementation of budget accountability budgets, and simultaneous budget evaluations had a significant positive effect on the performance of government agencies in the Regional Work Unit of the Badung Regency. Keywords : Management; planning; implementation; reporting; accountability.